Towards the identification of modifiable personal predictors of low back pain in nursing students - Mitchell, Timothy (Curtin University, 2008)
Low back pain (LBP) remains one of the most common and challenging primary care issues in the developed world. Manual occupations such as nursing are known to involve a high risk of occupational LBP, which is associated with enormous health care expenditure as well as indirect work and disability-related costs. Despite extensive efforts to reduce LBP in nurses, evidence supporting the efficacy of any specific intervention to prevent LBP is limited.The majority of LBP prevention strategies are directed at occupational risk factors in working nurses. However, as there is some evidence that LBP is already a significant problem in nurses prior to commencing full time employment, it is proposed that nursing students should be the focus of prevention interventions. This would require prevention interventions targeting personal rather than occupational LBP risk factors. As the best personal predictor of future LBP is currently a previous history of LBP, further investigation of modifiable personal LBP risk factors is required. Consequently, the aim of this doctoral research was to identify modifiable personal characteristics that predict LBP in nursing students.Firstly, a large survey was conducted on undergraduate nursing students and recently graduated nurses to determine patterns of LBP prevalence. Results from this study indicated that LBP prevalence was very high at the commencement of undergraduate training. Prevalence of LBP did not significantly change during nursing training, but did increase further in the first year of commencing work as a nurse. This increase may be partly explained by the reported increase in occupational exposure to bending and lifting. Age was consistent across the undergraduate year groups and did not influence these findings. It was concluded that nursing students would provide a sufficient number of new-onset LBP episodes (and thus sufficient statistical power) for a prospective study design. Further, as these nursing students were not yet exposed to the occupational LBP risk factors of working nurses, a clearer indication of the influence of modifiable personal factors on the development of LBP could be determined by examining a student cohort.A cross-sectional study investigating the influence of personal physical, psychological and social/lifestyle factors was then conducted on nursing students. Preliminary analysis revealed clear gender differences across multiple domains. Therefore, the focus of further analysis was on the larger female sample.In Part 1 of the cross-sectional study, an investigation of regional differences in lumbar spine posture and movement was undertaken. Analysis of spinal kinematics in this study supported and extended previous literature that has found global lumbar spine kinematics do not accurately reflect the kinematics of the upper lumbar or lower lumbar spinal regions in common postures and movements. Rather, these two regions have a degree of functional independence. This finding has implications for interpretation of measures of spinal posture, motion and loading. Further, body mass index influenced regional lumbar posture and movement, possibly representing adaptation due to load. It was concluded that regional rather than global lumbar spine measures needed to be investigated in further analyses of this doctoral research.In Part 2 of the cross-sectional study, personal characteristics associated with LBP were investigated. Approximately one third of all subjects reported significant LBP in the 12-months preceding the study. Analysis of factors associated with LBP supported the biopsychosocial nature of LBP. Higher stress levels and use of passive coping strategies, increased physical activity levels, holding the lower lumbar spine further from end-range flexion during functional tasks and increased age, all contributed independently to the presence of LBP. These findings supported the hypothesis that modifiable personal characteristics were associated with LBP.The importance of identifying sub-groups of LBP patients has become widely accepted. In Part 3, further exploratory analysis was conducted on this crosssectional data to determine if differences in physical and psychological characteristics were evident in two defined sub-groups of female nursing students with LBP. These sub-groups were based on O’Sullivan’s mechanism based classification system. Results indicated that two sub-groups of LBP subjects had differing physical and psychological characteristics associated with their LBP. Further, control subjects could be distinguished from each of these two sub-groups by different factors. These findings add validity to O’Sullivan’s LBP classification system. Further, the findings may suggest that different combinations of psychological and physical factors are linked to LBP in different sub-groups in this population, and therefore may require different intervention approaches based on these factors.In the final stage of this doctoral research, the cohort of female nursing students was followed prospectively for 12-months. The focus of further analysis was on identifying modifiable personal predictors in a sub-group of subjects with new-onset LBP. The results of this study strongly supported that personal factors from multiple domains are predictors of new-onset LBP. After controlling for previous LBP, age and body weight, regression analysis identified that smoking, increased physical activity levels (both exercise and spinal loading), higher stress levels, reduced back muscle endurance, greater posterior pelvic tilt in slump sitting and more accurate spinal repositioning in sitting were all independent predictors of new-onset LBP. These findings have implications for the development of prevention and management interventions for LBP in nurses.Results from this doctoral investigation support the multi-factorial and biopsychosocial nature of LBP. The important distinction of this research when compared to previous work is the selection of a cohort at the beginning of their working life, with a focus on modifiable personal, rather than occupational factors, associated with LBP. Factors from physical, psychological and social/lifestyle domains were all independently associated with significant new-onset LBP in female nursing students. Interventions utilising a prevention approach that targets modifiable characteristics, such as those identified in this cohort of nursing students, may have the potential to reduce the impact of occupational LBP in this group. These preliminary findings have important implications for future LBP research and clinical interventions.